(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
Professional skills have become a defining criterion of graduate quality in contemporary higher education, especially in economics, business, and accounting-related fields where disciplinary knowledge must be translated into communication, judgment, teamwork, analysis, self-management, and practice-oriented decision-making. The article examines the effectiveness of an integrative approach to professional skill development among undergraduate economics students in Uzbekistan. The design combined integrated courses, cross-functional learning tasks, practice-based assignments, portfolio work, reflective activities, and active learning methods that linked academic content with professional situations. A three-year quasi-experimental study was conducted at three universities with 375 full-time students, including 187 students in the experimental group and 188 in the control group. Data were collected through surveys, tests, observation, expert evaluation, academic records, practice reports, self-assessment, and supervisor assessment. The analysis relied on comparative procedures, descriptive statistics, mean-score calculations, and non-parametric testing.